PENGARUH DISCOVERY LEARNING MODEL TERHADAP KETERAMPILAN GERAKAN KAYANG PEMBELAJARAN SENAM LANTAI PADA SISWA KELAS XI DI SMA NEGERI 1 TEMPURAN - Eva Hayati; Setio Nugroho; Muhammad Mury Syafei (Universitas Hamzanwadi, 2026)
This study was motivated by the low level of kayang movement skills among 11th-grade students at Tempuran State High School 1, where 63.9% of students still struggled to perform the kayang movement using the correct technique, particularly in the initial position, execution, and final position. The purpose of this study was to determine the effect of applying the Discovery Learning Model on improving kayang movement skills in floor exercise. The study employed an experimental method using a one-group pretest-posttest design. The study sample consisted of 36 students selected using purposive sampling. The instrument used was a backbend skill test that had been validated through expert judgment and tested for reliability using Cohen’s Kappa (0.82). The intervention was administered over eight sessions spanning four weeks. Data analysis utilized descriptive statistics, the Shapiro-Wilk normality test, and the paired-sample t-test. The results showed an increase in the mean score from 59.19 on the pretest to 66.11 on the posttest (an increase of 6.92 points). The paired-sample t-test yielded a significance value of 0.000 (p < 0.05) with a Cohen’s d effect size of 3.76 (very large category). Based on these results, it can be concluded that the application of the Discovery Learning Model has a positive and significant effect on improving students’ floor exercise bridge movement skills.